Academic Senate Minutes 2008-04-24 - Academic Senate:::::::::
Chair's Report. Moment of silence for Dr. Barry Godolphin. Agenda amended and approved. Minutes of 3/20/08 approved. Update on WASC. Resolution re: Staffing Ratios in Student Counseling and Psychological Services approved. Resolution Combating Hate Crimes at SSU approved. Resolution commemorating the Anthropological Studies Center on its 35th year approved. Resolution endorsing CFA workshop Addressing Equity, Diversity, and Affirmative Action approved. Resolution on Blood Banks and Non-Discrimination approved. Revision to Academic Calendar Guidelines approved.